THE IMPACT OF ELECTRONIC ACADEMIC LEARNING MATERIALS ON ACADEMIC PERFORMANCE AMONG UNDERGRADUATES AT THE UNIVERSITY OF IBADAN, NIGERIA - Peter Babajide OLOBA; Runash RAMHURRY (International Journal of Social and Educational Innovation, 2025)
The reliance on electronic academic learning materials among students in tertiary institutions has become increasingly prevalent. However, this trend has led to unintended consequences, such as a declining reading culture and reduced use of traditional college libraries. This study investigated the use and accessibility of electronic academic learning resources and their impact on undergraduate academic performance at the University of Ibadan. Employing an exploratory cross-sectional research design, a sample of 600 undergraduate students was selected using the Yamane statistical formula, and data were collected through accidental sampling. A structured, closed-ended questionnaire was administered, and the data were analysed quantitatively using both descriptive and inferential parametric statistics. Findings revealed that 100% of respondents regularly accessed electronic academic learning materials, with no significant relationship between access and class background (R² = .034, p > .68). Regarding utilisation, 83.2% of the students relied on these resources for academic reading and assignments. The use of electronic academic learning materials significantly predicted utilisation patterns (R = .74, R² = .84, p < .000), with a mean utilisation score of M = 2.0. However, increased reliance on electronic materials was associated with reduced intention to use the library (M = 1.1) and a weakened reading culture (M = 2.0). The study concludes that undergraduate students at the University of Ibadan heavily rely on electronic academic learning materials, which may negatively impact library use and reading habits. It is recommended that university libraries adopt electronic-based models to attract student patronage and encourage library engagement. Furthermore, a systemic integration of technology into teaching, learning, and assessment practices is advocated to promote the effective and balanced use of academic resources, ultimately enhancing students' academic performance.